ANAPHORIC AND CATAPHORIC REFERENCES USED IN THE CHAPEL SHORT STORY - Ana Shofiana Jamilah; Agnes Larasati; Luthfi Nasiroh Khoirun Nisa (Universitas Duta Bangsa Surakarta, 2023)
This study aims to analyze the endophoric reference including the types of Anaphora and cataphoric reference that are contained in the short story titled